The Role of Ethics and Religion to Reduce The Corruption Level in Indonesia, Moderated by The Government Internal Control System - Mochamad Muslih; Haryono Umar (GoAcademica Research & Publishing, 2020)
The purpose of this study is to study the effect of ethics and religion on reducing corruption, moderated by the government’s internal control system. This study used quantitative method. The population is Indonesian society. The research sample is the academic community and auditors. The sample selection is done purposively. The data used is primary data. Data collection was carried out using an online questionnaire. A total of 108 respondents filled out a questionnaire created using Google forms. The results showed that ethics had no significant effect on reducing corruption, religion had no significant effect on reducing corruption, moderating government internal control systems on ethical influence on reducing corruption was not significant, and moderating government internal control systems (SPIP) on religious influence on reducing corruption was not significant. Subsequent researchers are advised to use cultural variables as one of the independent variables.